History of formation and development of the concept sphere education through modern scientific world picture - Serebrianska Іryna (Ukrainian linguistics, 2017)
The purpose of the article is to trace the path of national education from Kiev Rus to the Soviet Union. The task is to summarize the key events and key concepts in the history of the formation of education in Ukraine through the prism of language picture of the world of the Ukrainian people, as language reflects all problems of the nation at each historical stage of its development. Our study is relevant in terms of reformation of Ukrainian education and appropriate processes: the accession of Ukraine to the Bologna Process in 2005, implementation of the Law of Ukraine “On Higher Education” (2014), discussion of the draft of the new Law of Ukraine “On education”. The research is based on the analyses of the following texts: “Ukrainian Encyclopedia”, which presents the history of education in close connection with the general history of Ukraine, “History of Education in Ukraine” by S. Siropolko, “Ukrainian small encyclopedia”, ed. prof. J. Onatskyi, “Encyclopedia of History of Ukraine”. We have classified the language means of education representation into several thematic groups taking into account the time, geographical and political features of the country in each period. They include types of educational institutions of different levels, forms of authority and funding sources of educational institutions; education authorities; stages of education development; education regulations; cultural and educational organizations and their periodicals; student organizations and their periodicals. Information about the author: Іryna Serebrianska – PhD, Associate Prof., Poctdoctoral Student, Oles Honchar National University of Dnipro (Ukraine). E-mail: serebryanska@ukr.net __________ References • Usik Je. Ju. (ed.) (2007) Glossarij sovremennogo obrazovanija [Glossary of modern education]. Kharkov: Izdatelstvo NUA, 524 p. (in Russian). • Mjasnikov V.A. (2013) Svitovyj osvitnij prostir [The world educational space]. Osvitologija: khrestomatija: Navch. posibnyk dlja studentiv vyshhykh navchaljnykh zakladiv [Education: hrestomathy: textbook for university students]. Kyiv: Edelvejs, p. 41. (in Ukrainian). • Ognevjuk V. O. (2013) Evoljucijnyj postup osvity v konteksti osvitologiji [Evolutionary progress of education in the context of education]. Osvitologija: khrestomatija: Navch. posibnyk dlja studentiv vyshhykh navchaljnykh zakladiv [Education: hrestomathy: textbook for university students]. Kyiv: Edelvejs, p. 311-316. (in Ukrainian).